Optimization of Facilities and Infrastructure in Elementary Schools through Management of Facilities and Infrastructure - Chica Awaliyah; Frysca Amanda Putri; Tin Rustini (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
To produce quality young people, education is very important. Facilities and infrastructure in schools are one of the components that affect the quality of education. So, this article will discuss the importance of optimizing facilities and infrastructure in elementary schools through the management of facilities and infrastructure. It is expected to improve quality in optimizing facilities and infrastructure. This research method is a research using a qualitative approach which is carried out in order to find out the optimization of facilities and infrastructure through proper management of facilities and infrastructure.